2004
DOI: 10.1074/jbc.m406207200
|View full text |Cite
|
Sign up to set email alerts
|

Shared Transcriptional Signature in Caenorhabditis elegans Dauer Larvae and Long-lived daf-2 Mutants Implicates Detoxification System in Longevity Assurance

Abstract: In the nematode Caenorhabditis elegans, formation of the long-lived dauer larva and adult aging are both controlled by insulin/insulin-like growth factor-1 signaling. Potentially, increased adult life span in daf-2 insulin/ insulin-like growth factor-1 receptor mutants results from mis-expression in the adult of a dauer larva longevity program. By using oligonucleotide microarray analysis, we identified a dauer transcriptional signature in daf-2 mutant adults. By means of a nonbiased statistical approach, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
360
3
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(393 citation statements)
references
References 64 publications
25
360
3
5
Order By: Relevance
“…We have demonstrated heterogeneity much earlier in the lifespan. This heterogeneity potentially complicates the interpretation of microarray studies of aging that incorporate many individuals at sampled timepoints (Lund et al 2002;Budovskaya et al 2008;McElwee et al 2004). Our ability to detect these discrete sub-populations allowed us to isolate them and compare their transcriptional profiles, where hierarchical clustering and PCA showed that the two sub-populations were indeed (Durieux et al 2011) showed that mitochondrial signals from neurons can affect the organism's lifespan through their action in the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated heterogeneity much earlier in the lifespan. This heterogeneity potentially complicates the interpretation of microarray studies of aging that incorporate many individuals at sampled timepoints (Lund et al 2002;Budovskaya et al 2008;McElwee et al 2004). Our ability to detect these discrete sub-populations allowed us to isolate them and compare their transcriptional profiles, where hierarchical clustering and PCA showed that the two sub-populations were indeed (Durieux et al 2011) showed that mitochondrial signals from neurons can affect the organism's lifespan through their action in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of the genes in these clusters had been identified previously in other microarray analyses (Table 3). Other clusters included four broad functional categories known to be involved in the aging process: heat-shock proteins (HSPs), cytochrome P450 family oxidases (P450 and sterol oxidases), insulin/IGF-1 signaling pathway components (Lund et al 2002;Murphy et al 2003;McElwee et al 2004, and genes broadly affecting mitochondrial function (Feng et al 2001;Lee et al 2003;Dillin et al 2002). In each functional cluster, our gene list included a number of genes not previously identified in other microarray studies of aging.…”
Section: Molecular Basis For Morphological Age Statesmentioning
confidence: 99%
“…These include cytochrome P450-dependent monoxygenases (CYPs), and UDP-glucuronosyltransferases (UGTs) (Wang and Kim, 2003) as well as short-chain dehydrogenases/reductases (SDRs) (McElwee et al, 2004) and glutathione S-transferases (GSTs) (Jones et al, 2001). CYPs are involved in the biosynthesis or biodegradation of a range of endogenous lipophilic substrates such as steroids, fatty acids and aromatic compounds and also in the biodegradation of xenobiotics.…”
Section: Stress Resistance Cellular Maintenance and Detoxification Pmentioning
confidence: 99%
“…Some dauer-specific processes are reiterated in long lived daf-2 adult nematodes Genome-wide surveys of transcriptional changes resulting from reduced signalling through the DAF-2 insulin/IGF-1 receptor in long-lived daf-2 adult nematodes have been carried out using microarray (McElwee et al, 2003(McElwee et al, , 2004Murphy et al, 2003) and SAGE (Halaschek-Weiner et al, 2005) analyses. Although there is some overlap between the gene sets identified in the different experiments, a high proportion of genes is uniquely identified in each study.…”
Section: Stress Resistance Cellular Maintenance and Detoxification Pmentioning
confidence: 99%
See 1 more Smart Citation